Faktor-Faktor Yang Berhubungan Dengan Kejadian Diare Pada Anak Usia 1-2 Tahun Di Ruang Matahari Rawat Inap Anak RSUD Leuwilianh Tahun 2021: Factors Related to Diarrhea in Children Aged 1-2 Years at Matahari Enhancement Room, Leuwiliang Hospital in 2021 - Kulsum, Umi (Dohara POAJ, 2022)
Introduction: The Household Health Survey (SKRT), mortality studies, and basic health research from year to year found that diarrhea is still the main cause of under-five mortality in Indonesia. The main cause of death due to diarrhea is improper management both at home and in health facilities. To reduce deaths due to diarrhea, fast and appropriate management is needed. The purpose of this study was to determine the factors associated with the incidence of diarrhea in children aged 1-2 years in the inpatient solar room at Leuwiliang Hospital in 2021. Methods: This study used a quantitative research design with the cross-sectional method, while the sample in this study was 60 patients with toddlers aged 1-2 years, who experienced diarrhea in the period August 2021. The data collection technique used a questionnaire. The statistical test used was the chi-square test using SPSS version 18 software. Results: The results of this study showed a relationship between the incidence of diarrhea and with measles immunization factor with an OR value of 15,333 and there was a relationship with complementary feeding with an OR value of 33,333. The relationship with family income also obtained an OR value of 3,365 with a P-value of 0,027. Discussion: The conclusion of this study is that there is a relationship between the measles vaccination, the appropriateness of complementary feeding, and family income to the incidence of diarrhea in children aged 1-2 years in the Matahari room at the Leuwiliang Hospital in 2021. Of the 60 children who did not have recurrent diarrhea, most of them did not get measles immunization (38,3%), did not get complimentary feeding that was not appropriate (41,7%), and came from a family with insufficient income (23,3%).